Pemetaan Sebaran Titik Hotspot Menggunakan Arcgis di Kota Banjarbaru Tahun 2019-2023 - Ajeng, Ajeng; Rosalina Kumalawati; Nurlina, Nurlina; Inu Kencana Hadi (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Hotspot point mapping is mapping in which to find out which areas have the largest distribution of hotspot points and make it possible for these areas to be prone to fire, this research uses a literature study method. In processing the map the author used data from the Sipongi website (Early Detection Information System for Controlling Forest and Land Fires) to determine Hotspot points in Banjarbaru City and the data obtained was processed using Arcgis 10.8 software. Based on map results that have been processed with data for 2019-2023, Lianganggang District is the district with the most hotspots at 46 points. Mapping the distribution of hotspots is an important step in understanding forest and land fire patterns and identifying areas that are vulnerable to these events. There are several factors that allow forest fires to occur apart from human activities, other activities such as natural factors from the dry season can also cause forest and land fires. This research aims to map the distribution of hotspot points in Banjarbaru City during the period 2019 to 2023. Hotspot point data was obtained from remote sensing satellites which were then analyzed using GIS (Geographic Information System) techniques to produce a hotspot distribution map. It is hoped that future research can use more sophisticated technology to map the distribution of hotspot points over a certain period of time, and it is also hoped that the results of this research can be useful for local government agencies with an interest in handling forest and land fires.